Polarisasi gender dalam efektivitas eWOM: Studi tentang peran kepercayaan dalam membentuk niat beli online - Irawan, Indra Ade (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2025)
This study aims to analyze the differences in the mechanisms of electronic word-of-mouth (EWOM) influence on purchase intention based on gender, by examining the mediating role of trust. Additionally, the study examines how the relationships between eWOM, trust, and purchase intention vary by gender. This study employed a survey of 235 university students as respondents, utilizing Structural Equation Modeling (SEM) analysis techniques to investigate the relationships between variables. The results indicate that at the aggregate level, eWOM has both direct and indirect effects on purchase intention, mediated through trust. Segmentation analysis revealed a different pattern: in women, eWOM primarily operates through trust formation, while in men, this relationship was not significant. These findings have important theoretical implications regarding the need for a gender-specific contextual information processing model, as well as practical implications for marketers developing differentiated eWOM strategies, focusing on building credibility for female consumers and exploring alternative approaches for male consumers. This study also opens up opportunities for further research on gender-specific moderating variables and psychological mechanisms in the context of digital marketing.